MO854PHYSICAL ACTIVITY IN CHRONIC HEMODIALYSIS PATIENTS: ABOUT 71 CASES. (29th May 2021) - Chemli, Imen; Ayed, Amel; Sinda, Ayed; Ben salem, Meriem; Ben salah, Manel; Handous, Insaf; Letaief, Ahmed; Hamouda, Mouna; Aloui, Sabra; Skhiri, Habib
Abstract: Background and Aims: physical activity is generally impaired in the chronic hemodialysis patient. Studies confirm the benefit of maintaining or improving physical activity in these patients. For this reason, our study aims to assess physical inactivity in chronic hemodialysis patients using a physical activity score: DIJON score and to identify the factors linked to a decrease in physical activity . Method: this is a descriptive and analytical cross-sectional study carried out at the hemodialysis center of Fattouma Bourguiba hospital in Monastir. We used the DIJON questionnaire to measure physical activity: daily activities, sports or leisure. The reference values for the level of physical activity are 0-10 (low), 10-20 (medium); and 20-30 (high). Results: our study included 71 patients. The middle age was 46.62 + - 15.34 years. 69% of patients were male. The overall physical activity level was high at 22.75 + -1.99 in 28.2% of patients, medium at 13.75 + -3.65 in 33.8% of patients and low at 5.56 + -2.91 in 38% of hemodialysis patients. Analysis in multiple linear regression showed that the variables that explained the DIJON score in our population are in order of contribution: pre-dialytic uremia (β = 0.433; t = 2.99; p = 0.005), cardiac diseases(β = 0.305; t = 2.074; p = 0.044), the KT/V ratio (β = -. 858; p = -1.915; p = 0.063), the PRU (β = 1.21; t = 1.885; p = 0.066), anemia (β = 0.211; t = 1.704; p = 0.096), comorbidity evaluated by Charlson score (β = -. 461; t = -1.414; p = 0.165). Conclusion: our results showed that the level of physical activity is linked to many factors, some of which are modified. So, prescribing an adapted and personalized program will improve the prognosis and the quality of life of our patients.